Is surgical excision necessary for the treatment of Granulomatous lobular mastitis? - Young Duck Shin; Sung Su Park; Young Jin Song; Seung-Myoung Son; Young Jin Choi (BMC, 2017)
Abstract Background We aimed to investigate the role of surgical excision in treating granulomatous lobular mastitis. Methods We performed a retrospective chart review of patients with granulomatous lobular mastitis treated from March 2008 to March 2014. We analyzed clinical features and therapeutic modalities and compared the patient outcomes based on treatment. Results During the study period, a total of 34 patients were diagnosed with granulomatous lobular mastitis and treated. Initial treatments included wide excision (18), oral steroids after incision and drainage (14), and antibiotic therapy (2). The patients receiving only antibiotic therapy showed no improvement after 1 month and wide excision was then performed. Wide excision resulted in nine case of delayed wound healing with fistula. These patients were treated with oral steroids for 1.5-5 months, with subsequent improvement. Overall, 11 out of 20 patients who had underwent wide excision showed improvement without additional treatment. Fourteen patients who had initially received oral steroids for 1 to 6 months (average, 2.8 months) after incision and drainage showed complete remission. During the median follow-up period with 45.5 months (range, 22-98 months), six patients (17.6%) experienced recurrence. Wide excision group experienced recurrence in five (25%) and steroid and drainage group experienced recurrence in one (7.1%). All six recurrences responded to additional steroid therapy for average 3.5 months. Most wide excision group left extensive breast scarring with deformation that was not in steroid and drainage group. Conclusions Wide excision resulted high recurrence than steroid and drainage group and left extensive scarring. Steroid therapy with or without abscess drainage may be the first choice of treatment for majority cases with granulomatous lobular mastitis.